2023
DOI: 10.1097/psy.0000000000001229
|View full text |Cite
|
Sign up to set email alerts
|

Recovery Sleep After Sleep Restriction Is Insufficient to Return Elevated Daytime Heart Rate and Systolic Blood Pressure to Baseline Levels

Abstract: Objective: Sleep restriction alters daytime cardiac activity, including elevating heart rate (HR) and blood pressure (BP). There is minimal research on the cumulative effects of sleep loss and the response after subsequent recovery sleep on HR and BP. This study examined patterns of HR and BP across baseline, sleep restriction, and recovery conditions using multiple daytime cardiac measurements. Methods: Participants (15 healthy men, mean [standard deviation] = 22.3 [2.8] years) completed an 11-day inpatient p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The authors concluded that 1) ad lib weekend sleep failed to prevent metabolic dysregulation during a repeated pattern of insufficient sleep and weekend recovery sleep ( Depner et al, 2021 ) and 2) the effects of insufficient sleep, with or without weekend ad lib sleep, on a 24-h pattern of energy balance were not dissimilar ( Depner et al, 2019 ). Another example is the study by Reichenberger et al (2023 ), who found an increase in the heart rate and systolic blood pressure following successive nights of sleep restriction, and neither the heart rate nor systolic blood pressure recovered to baseline levels following two nights of ad lib sleep.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that 1) ad lib weekend sleep failed to prevent metabolic dysregulation during a repeated pattern of insufficient sleep and weekend recovery sleep ( Depner et al, 2021 ) and 2) the effects of insufficient sleep, with or without weekend ad lib sleep, on a 24-h pattern of energy balance were not dissimilar ( Depner et al, 2019 ). Another example is the study by Reichenberger et al (2023 ), who found an increase in the heart rate and systolic blood pressure following successive nights of sleep restriction, and neither the heart rate nor systolic blood pressure recovered to baseline levels following two nights of ad lib sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, chronic sleep loss is a serious public health issue associated with CV disease (Cappuccio et al., 2011 ; Liew & Aung, 2021 ; Liu & Chen, 2019 ; Mullington et al., 2009 ; Tobaldini et al., 2017 ), as well as numerous other adverse health consequences including cancer, diabetes, Alzheimer's disease, obesity, morbidity, and mortality (Gallicchio & Kalesan, 2009 ; Mullington et al., 2009 ; Niu et al., 2022 ). In response to the two most commonly experienced types of sleep loss, total sleep deprivation (TSD) and sleep restriction, CV measures such as stroke volume (SV), left ventricular ejection time (LVET), systolic blood pressure (SBP) and diastolic blood pressure (DBP), heart rate (HR), cardiac index/cardiac output (CI/CO), systemic vascular resistance index (SVRI), and mean arterial pressure (MAP), have shown inconsistent findings, with some studies reporting alterations, and others showing no changes (Cernych et al., 2021 ; Kato et al., 2000 ; Keramidas et al., 2018 ; Krause et al., 2023 ; Kuetting et al., 2019 ; Lü et al., 2018 ; Mikulski et al., 2006 ; Muenter et al., 2000 ; Mullington et al., 2009 ; Papacocea et al., 2019 ; Reichenberger et al., 2023 ; Sauvet et al., 2010 ; Sunbul et al., 2014 ; Yamazaki, Rosendahl‐Garcia, et al., 2022 ; Zhong et al., 2005 ).…”
Section: Introductionmentioning
confidence: 99%